Kritik Sanad Hadis Khitan Terhadap Perempuan sebagai Kehormatan - Abdul Rahman Sakka (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2021)
Hadith relating to woman circumcision as honor used as the argument in the MUI fatwa number 9a of 2008 has received a lot of criticisms. Thus, it is important to re-research as a form of follow-up to the previous research. This research is a research library with critical analytical methods on the hadith sanad with the aim of knowing with certainly the quality and quantity of hadith and its authenticity. Based on the results of the study, it was found that there were ten transmission routes listed by the four mukharrij rulers; that is; Ahmad bin Hanbal, Ibn Abi Syaibah, al-Tabrani, and al-Baihaqi. Of the ten lines of transmission, seven are hadiths marf'u and three lines of hadith mauqÅ« f. In terms of quantity ('adad al-á¹uruq), this hadith is classified as a famous hadith because it is narrated by a minimum of four narrators in each sanad á¹abaqah (level). Meanwhile, in terms of quality, this hadith is defined as a very weak hadith (á¸a'Ä«f jiddan) because of the inherent defects involved in the narration. Thus it cannot be used as the main argument to justify circumcision against women and also cannot be used as an argument for woman circumcision for reasons of honor. This hadith can only be a reinforcement of the authentic and hasan traditions which talk about female circumcision. The inclusion of this hadith in the MUI fatwa as the main argument for justifying circumcision for women needs to be reviewed considering that this hadith is very weak..